Role of work-family facilitation in the relationship between environment factors and outcomes in work and non-work domains. - Gopalan, Neena (Kansas State University, 2011)
Literature on work and family, the two important domains in an individual’s life, has focused heavily on the conflicts that could occur when individuals try to juggle between their responsibilities in the two domains. Lately, there has been enthusiasm to also study the facilitation aspects that could result from being engaged in both domains. This dissertation empirically tests the Resources-Development-Gain model (RGD), a recently developed work and family facilitation model, which include work and non-work factors that can bring facilitation. Over 500 academic faculty members from four universities completed an online survey comprised of demographic items, family and work variables, variables to measure facilitation, outcome variables in both domains, and personality variables. The hypothesized model (model 1) was analyzed using AMOS, and was found to be a poor fit. Personality factors included as moderators in the facilitation process were found to be non-significant and hence dropped from the modified model (Model 2). This was a significantly better fit. Model 3 was analyzed to see if a better fit would be obtained when personality variables were directly connected to outcome variables. As Model 3 did not add anything significant, Model 2 was accepted. The findings suggest that faculty tenure influenced their turnover intentions, with new academic faculty and full professors showing lower turnover intentions. Family support brought facilitation from one’s family to work and contributed to life satisfaction, while organizational support contributed to facilitation from one’s work to non-work life. No significant overlaps were found between work and family domains in the facilitation stage, but were observed at the outcome levels. Thus, job satisfaction in the work domain contributed to overall life satisfaction in the family domain. Satisfaction in one’s personal relations also tended to influence one’s turnover decisions. Future directions for research and recommendations are discussed.
Keywords: Work Family Facilitation; Resource-Gain-Development model (RGD); Turnover; Life satisfaction; Job satisfaction; Personality factors; Management (0454); Psychology (0621)